Pamphagidae (Orthoptera: Acridoidea) from the Palaearctic Region: taxonomy, classification, keys to genera and a review of the tribe Nocarodeini I.Bolívar - Ünal, Mustafa (Zootaxa, 2016)
The very rich material of Palaearctic Pamphagidae preserved in the collections including the type specimens of all taxa, the historical unidentified specimens and newly collected material have been studied. 58 genera and 295 species and subspecies are listed. The higher classification of the family is reviewed mainly based on the male phallic complex as well as the traditional and some new external characters. The tribe Haplotropiidini is transferred to the subfamily Thrinchinae. Previously synonymized subfamily Tropidaucheninae is validated as an independent tribe of Pamphaginae. The tribe Nocarodeini is taxonomically reviewed except the genus Bufonocarodes Mistshenko. The male phallic complex is also used as one of the main characters in decisions of the genus group taxa. The following 10 genera are synonymized: Pseudotmethis Bey-Bienko, 1948 and Paratmethis Zheng & He, 1996 (with Filchnerella Karny, 1908), Sinotmethis Bey-Bienko, 1959 and Kanotmethis Yin, 1994 (with Beybienkia Tsyplenkov, 1956), Paktia Pfadt, 1970 (with Mistshenkoella Cejchan, 1969), Pseudosavalania Demirsoy, 1973 (with Paranocarodes I. Bolívar, 1912), Nocaropsis Ramme, 1951 (with Paranothrotes Mistshenko, 1951), Paranocaracris Mistshenko, 1951 and Oronothrotes Mistshenko, 1951 (with Nocaracris Uvarov, 1928) and Savalania Mistshenko, 1951 (with Nocarodes Fischer von Waldheim, 1846). The genera Mistshenkoella Cejchan and Cryptonothrotes La Greca are proposed as subgenera of Saxetania Mistshenko. The following genera are divided: Eremocharis Saussure into 4 species groups, Paranocarodes I. Bolívar into 2 species groups, Paranothrotes Mistshenko into 4 species groups, Nocaracris Uvarov into 7 species groups and Nocarodes Fischer von Waldheim into 4 species groups. The following 24 species and subspecies are synonymized: Tmethis cinerascus cyanipes Werner, 1939 [with Eremopeza angusta (Uvarov, 1934)], Iranotmethis cyanipennis cyanipes Bey-Bienko, 1951 [with Iranotmethis cyanipennis iranicus (Werner, 1939)], Eremocharis granulosa roseipes Uvarov, 1943 [with Eremocharis granulosa granulosa (Walker, 1871)], Eremocharis subsulcata minor Cejchan, 1969 (with Eremocharis maior Ramme, 1952), Asiotmethis limbatus motasi Ramme, 1951 [with Asiotmethis limbatus (Charpentier, 1845)], Tropidauchen marginatum Bolívar, 1912 (with Tropidauchen escalerai Bolívar, 1912), Paranocarodes straubei serratus Uvarov, 1949, Paranocarodes straubei insularis Ramme, 1951 and Paranocarodes fieberi mytilenensis Ramme, 1951 [with Paranocarodes fieberi (Brunner von Wattenwyl, 1882)], Paranocarodes atympanicus Ramme, 1951 (with Paranocarodes tolunayi tolunayi Ramme, 1949), Paranocarodes cilicicus Ramme, 1951 (with Paranocarodes lubricus Mistshenko, 1951), Paranothrotes opacus hakkariana Demirsoy, 1973 [with Paranothrotes opacus opacus (Brunner von Wattenwyl, 1882)], Paranothrotes tenuicornis sordidus Mistshenko, 1951 and Paranothrotes iranicus (Ramme, 1951) (with Paranothrotes tenuicornis Mistshenko, 1951), Paranothrotes elbursianus (Ramme, 1951) [with Paranothrotes demawendi (Ramme, 1951)], Paranocarodes aserbeidshanicus Ramme, 1951 [with Paranothrotes margaritae (Miram, 1938)], Nocaracris burri obscurata Ramme, 1951 [with Nocaracris furvus furvus (Mistshenko, 1951)], Paranocaracris rimansonae ventosus Mistshenko, 1951 [with Nocaracris rimansonae (Uvarov, 1918)], Paranocaracris rigidus Mistshenko, 1951 (with Nocaracris tauricolus Ramme, 1951), Nocaracris cyanipes tristis Ramme, 1951 [with Nocaracris cyanipes (Motschulsky, 1846)], Nocarodes armenus Ramme, 1951 (with Nocarodes serricollis Fischer von Waldheim, 1846), Nocarodes specialis Mistshenko, 1951 [with Nocarodes iranicus (Werner, 1939)], Nocarodes gibbosus Mistshenko, 1951 (with Nocarodes humerosus Mistshenko, 1951), Nocarodes urmianus carinatus Mistshenko, 1951 (with Nocarodes urmianus Ramme, 1939). One new genus in the tribe Nocarodeini, Turkanocaracris Ünal gen. nov., and the following 29 new species and subspecies in four tribes are described: Eremopeza soltanii Ünal, sp. nov., Eremopeza kashmirensis Ünal, sp. nov., Eremocharis subsulcata beccalonii Ünal, ssp. nov., Orchamus massai Ünal, sp. nov., Paracinipe suezensis Ünal & Massa, sp. nov., Saxetania (Mistshenkoella) gorochovi Ünal, sp. nov., Paranocarodes anatoliensis anamas Ünal, ssp. nov., Paranothrotes buzuldagi Ünal, sp. nov., Paranothrotes dentatus Ünal, sp. nov., Paranothrotes eximius bitlis Ünal, ssp. nov., Paranothrotes siirt Ünal, sp. nov., Nocaracris furvus kazdagi Ünal, ssp. nov., Nocaracris istanbul Ünal, sp. nov., Nocaracris tunceli Ünal, sp. nov., Nocaracris tardus Ünal, Bugrov & Jetybayev, sp. nov., Nocaracris emirdagi Ünal, sp. nov., Nocaracris cejchani Ünal, sp. nov., Nocaracris judithae Ünal, sp. nov., Nocaracris minutus Ünal, sp. nov., Nocaracris karadagi Ünal, sp. nov., Nocaracris palandoken Ünal, sp. nov., Nocaracris monticolus Ünal, sp. nov., Nocaracris van Ünal, sp. nov., Nocaracris dilekensis Ünal, sp. nov., Nocaracris karshitoros Ünal, sp. nov., Nocaracris goektepe Ünal, sp. nov., Nocaracris crassipes Ünal, sp. nov., Turkanocaracris levigatus Ünal, sp. nov., Turkanocaracris davisi Ünal, sp. nov. Lectotypes are designated for the following 12 species: Strumiger desertorum desertorum Zubovski, 1896, Ocnerosthenus brunnerianus (Saussure, 1887), Orchamus gracilis (Brunner von Wattenwyl, 1882), Saxetania iranicum (Werner, 1939) [syn. of Saxetania (s.str.) cultricolle (Saussure, 1887)], Paranocarodes straubei (Fieber, 1853), Paranocarodes fieberi (Brunner von Wattenwyl, 1882), Paranothrotes shelkovnikovi (Uvarov, 1918), Paranothrotes nigripes (Stshelkanovtzev, 1916), Eunothrotes derjugini Adelung, 1907, Nocaracris rimansonae (Uvarov, 1918), Nocaracris tridentatus (Stshelkanovtzev, 1916) and Araxiana woronowi (Uvarov, 1918). Many species are given in new combinations and new statuses. Some taxa are proposed as reverted combinations, reverted statuses, reverted genera, species and subspecies. Nomenclatural problems are discussed under the relevant taxa. The authorship of 4 species are discussed and changed as follow: Eremopeza festiva (I. Bolívar, 1884), Paranocarodes tolunayi tolunayi Ramme, 1949, Nocaracris rubripes (Motschulsky, 1846), Nocaracris cyanipes (Motschulsky, 1846). Identification keys for subfamilies, tribes and genera (except the N. African and European genera of Pamphagini) and for each level of the tribe Nocarodeini are prepared. This study is also a review of the Pamphagidae species of Turkey. Therefore all Turkish species are studied in detail except the two genera recently revised by the author, Glyphotmethis Bey-Bienko and Asiotmethis Uvarov. Geographically this paper includes all Pamphagidae species of the following countries and regions: Bulgaria, Turkey, Cyprus, Syria, Israel, Palestine, Jordan, Iraq, Armenia, Georgia, Nakhichevan, Azerbaijan, Pakistan, Greece (except one species), Lebanon (except two species), Arabian Peninsula (except one species), Afghanistan (except some Saxetania) and Iran (except some Saxetania and Tropidauchen). In addition, 848 original figures including 10 distributional maps are provided.